Long-term treatment with tocilizumab in giant cell arteritis: efficacy and safety in a monocentric cohort of patients. Issue 2 (15th May 2020) - Regola, Francesca; Cerudelli, Elisabetta; Bosio, Giovanni; Andreoli, Laura; Tincani, Angela; Franceschini, Franco; Toniati, Paola
Abstract: Objective: The efficacy of tocilizumab (TCZ) in GCA is supported by two randomized controlled studies, in which TCZ allowed remission to be achieved after 52 weeks of treatment. However, after discontinuation of treatment, half of the patients relapsed. The aim of this study was to analyse the efficacy and safety of long-term treatment with TCZ and the role of fluorodeoxyglucose (FDG)-PET/CT scanning in the follow-up of these patients. Methods: We collected the clinical data of a monocentric cohort of GCA patients retrospectively. Results: Thirty-two patients were treated with TCZ [25 males and 7 females; age = 74 (59–81) years]. Most of them achieved and maintained clinical remission (1 month: 69%; 3 months: 91%; 6 months: 96%; 12 months: 100%), with serological and FDG-PET/CT scan improvement and a reduction of concomitant glucocorticoid therapy. Nineteen patients were treated for >52 weeks, and in 13 of them a dose tapering was performed, whereas in 2 cases TCZ was suspended for disease remission. Only two patients relapsed: one during TCZ tapering and one after TCZ discontinuation. Ten cases of mild infections and a case of urinary sepsis were reported; in patients treated for >1 year there was no increase in the incidence of side effects compared with patients treated for <12 months. Conclusion: In our cohort of patients, we confirmed the efficacy of TCZ in the induction and maintenance of remission of GCA, demonstrating an important steroid-sparing effect and a good safety profile. Long-term treatment seems to prevent relapse of the disease, suggesting that TCZ treatment can be continued for >52 weeks with efficacy and safety.